The Role of GnRH Agonist Therapy and Hysterosalpingography (HSG) in Diagnosing and Treating Tubal Factor Infertility - Dipti Katre; Namrata Choudhary; Ashish Prakash Anjankar; Aakash More; Sudhanshu Dakre (Journal of Pharmacy and Bioallied Sciences)
The paper describes the treatment of a 27-year-old woman with a history of infertility, heavy menstrual periods, and severe endometriosis with bilateral hydrosalpinx. The patient received hormonal treatment with triptorelin acetate, a GnRH agonist, to treat her endometriosis and regulate her menstruation. Hysterosalpingography confirmed the presence of bilateral hydrosalpinx, thus suggesting IVF as the most suitable method to conceive. The patient went through a long protocol using GnRH agonist and 14 oocytes were retrieved from her with 10 being fertilized. To avoid ovarian hyperstimulation syndrome (OHSS), all the embryos were frozen and thawed after six months of hormone replacement therapy for the preparation of the endometrium, and a single blastocyst was transferred. The patient conceived, and a subsequent β-hCG level of 256 mIU/mL proved good pregnancy status 14 days after the embryo transfer. This case demonstrates how a personalized and holistic treatment approach to the management of infertility, especially in patients with such conditions as endometriosis and hydrosalpinx, can be very fruitful.